O futuro da Amazônia: horizonte de expectativa de Arthur Reis (década de 1950) - Sidney Lobato (Confins)
In this article we intend to understand the Amazon future vision of Arthur Reis historiographical texts. Analyzing several works wrote by Reis during 1950s, we concluded that, to him, this region was foreordained to be a “developed” society, with agricultural economy. Seeing coeval intellectual production, we could also conclude that too many writers and political leaders shared Reis horizon of expectation. We emphasize a very extensive utilization of this future vision which goal was to transform deeply the regional life style.